Adverse Drug Reactions and Outcome Analysis of MDR Tb Patients on Dots Plus Regimen - Vishakha K Kapadia; Sanjay B Tripathi (National Journal of Community Medicine, 2016)
Introduction: The emergence of drug resistant mycobacteria has become a significant public health problem world over creating an obstacle to effective TB control. Present study was conducted to evaluate pattern and frequency of adverse drug reactions (ADR) of CAT IV, to analyze demographic, radiological and bacteriological profile and treatment outcome in MDR TB patients.